Changes in Polyphenolic Concentrations of Table Olives (cv. Itrana) Produced Under Different Irrigation Regimes During Spontaneous or Inoculated Fermentation - Perpetuini, Giorgia; Caruso, Giovanni; Urbani, Stefania; Schirone, Maria; Esposto, Sonia; Ciarrocchi, Aurora; Prete, Roberta; Garcia-Gonzalez, Natalia; Battistelli, Noemi; Gucci, Riccardo; Servili, Maurizio; Tofalo, Rosanna; et al. (Frontiers in Microbiology, 2018)
Irrigation is widely used for the production of table olives because it increases fruit size and yield. However, irrigation also determines less accumulation of total phenols, an increase in water content, a decrease of firmness, lower concentrations of soluble sugars in the mesocarp, thus positively or negatively affecting the fermentation process for the production of table olives. In this study we tested the hypothesis that green fruits of cultivar Itrana obtained by different irrigation regimes had different phenolic concentration that responded differentially to spontaneous or inoculated fermentation. Fruits were harvested from two orchards in the Latina province of Latium, Italy, which had been irrigated with different volumes of water during the growing season to compare the evolution of spontaneous and inoculated fermentation processes. We measured fruit characteristics at harvest, changes in the concentrations of secoiridoids and lignans, and main microbial groups abundance during fermentation. At harvest and during fermentation the concentration of phenolic compounds was higher in fruits sampled from trees that had received less water in the field. Differences were observed between spontaneous and inoculated fermentations, with a prevalence of lactic acid bacteria (LAB) in inoculated samples. In particular, oleuroperin concentration completely disappeared only from samples inoculated by the two selected strains used as starters. The inoculum with selected LAB positively influenced the fermentation process of green olives, whereas the irrigation regime previously experienced by trees did not alter fermentation.